Caring for the carer in Pediatric and Neonatal icus - Kovács, Maria Julia; Esslinger, Ingrid; Vaiciunas, Nancy; Moreira Souza, Telma (O Mundo da Saúde, 2008)
Death is seen as a shame and a failure, an event to be fought at all means. The nursing team deals with loss, pain, death and its fight in its daily routine. After having taken part in the course: “Health professionals and education: Death in their daily practice”, a team of nursing professionals of a public hospital of São Paulo asked for the contribution of the professionals of the Laboratory of Studies on Death of the Institute of Psychology of USP to deal with the above situations, and this motivated the creation of the project “Caring for the carer in the hospital context”. In this article we present a work modality called Thematic Meetings with the following objectives: a) “warm-up” of the team in the central subject to be approached; b) deepening on the subject brought by the team; c) planning the care action thought by the group. The activities were: verbal relaxation, disconnection, introspection, participation in expressive activities and stories. The work was carried through in the Pediatric and Neonatal ICU of the School Hospital of the University of São Paulo (UTIP/N-HU-USP), from the assistance to a child with a serious congenital disease that demanded internment in an Intensive Care Unit. 10 professionals of the nursing team of the unit had taken part. The initial demand was to learn to deal with death for “not feeling bad about it” and preventing an intense involvement with its patients. Among the presented subjects in this thematic meeting are the following: 1) More identification with the role of mother than with the one of nurse; 2) Disruption of bonds; 3) the world of the patient (interned in ICU since her birth); 4) the inexorable: death; 5) the inner child. It was possible to deal with the feelings of each member of the group and those of the group as a whole, perceiving the potentialities and the fragilities of the team of this situation, respecting the limits of each person, opening space for planning actions and strategies of care inside the institution.